Camponeses, Projetos e o Futuro - Baptista, Fernando Oliveira (Trabalhos de Antropologia e Etnologia, 2020)
In the most developed countries, in the last seven decades, peasants become modernized farmers or have left villages. In the Southern countries, they are unable to reconvert or leave agriculture. They stayed in the villages, with a constantly growing population and always in a subordinate and fragile position. They are now mostly a population left over from the globalized economy. In these ways, the peasants sometimes revolted, resisted but were never in a postion to hegemonize and to govern the state. However, projects persist that aim to make peasants in control of their own destiny. Of these, we will mention two that have shown that, for the peasants, these proposals do not appear as a destination but only as possibilities to compare with other alternatives.